Faktor yang Mempengaruhi Pendapatan Nelayan di Kacamatan Genuk Kota Semarang - Jihan Ayu Nabila; Siti Aisyah (Ekonomis: Journal of Economics and Business, 2023)
One of the agricultural sub-sectors that has the potential to develop in Indonesia is fisheries. This is due to the fact that most of Indonesia's territory is water, which produces a variety of marine product commodities that have high economic value. Fishermen in Genuk District have the potential to get abundant marine products but are constrained by limited equipment to catch marine products that still use simple machines. This study aims to determine how much influence age, wealth, working hours, and catches have on the income of fishermen in Genuk District, Semarang City. Data was obtained by distributing questionnaires to respondents and processed using multiple linear regression analysis method. The results of the study are that capital has a significant negative effect on the income of fishermen in Genuk District, Semarang City and catch yields have a positive and significant effect on the income of fishermen in Genuk District, Semarang City, while age and working hours have no significant effect on the income of fishermen in Genuk District, Semarang City. Suggestions for the Semarang City Government should provide infrastructure and assistance in the form of grants for more modern fishing gear and better technical guidance so that the potential of natural resources can be utilized more optimally and the welfare of fishermen will improve.